A future concern of iterative learning control : A survey. Issue 6 (18th August 2021) - Riaz, Saleem; Hui, Lin; Aldemir, Mehmet Serif; Afzal, Farkhanda
Abstract: The main idea of iterative learning control (ILC) was exposed when Arimoto's first paper was published. Industrial tasks mainly in repetition are controlled by an iterative teaching controller in both iteration and time-domain which makes ILC unique. ILC is becoming very popular among control engineers because of its very simple and effective control techniques. This paper describes the basic key knowledge about ILC and its types of applications. The core concern of this paper is to elaborate and explore the future scope and key application areas of iterative learning control in engineering as well as other all subjects of interest.